Further investigations on the influence of scale-up of a high shear granulator on the granule properties - Rahmanian, N. (2013)
This study focuses on the characterisation of strength, density, and size of granules produced in various scales of a high shear granulator. Calcium carbonate (Durcal 65) was used as the feed powder and aqueous polyethylene glycol (PEG 4000) as the binder. The dried granules were analysed for their strength, density, size distribution, and wall make-up. Granules were produced in granulators with four scales, 1, 5, 50, and 250 L under three scale-up rules of constant tip speed, constant shear stress, and constant Froude number. The results show that regardless of equipment scale, increasing the impeller speed has a great effect on crushing strength and stress. The underlying cause is an increase in granule density due to more consolidation at higher impeller speeds. Wall make-up is significantly reduced to less than 5 as the scale is increased from 1 to 250 L. The results of this study corroborate our previous findings that the constant tip speed rule is the best criterion for scale-up of high shear granulators. Â© 2013 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences.